What's Right and Wrong with “No Endorsement” - Thomas C. Berg (Washington University Journal of Law & Policy, 2006)
Contrary to Professor Wexler, I argue that unless the endorsement test is properly understood and limited, it has the critical flaw of putting the Establishment Clause at war with the other religion guarantee of the First Amendment, the Free Exercise Clause. If the Establishment Clause forbade government endorsement of religion in all contexts, it would undermine the government’s ability to give special accommodation to religious practice and thus would severely impair free exercise values. “No endorsement of religion” thus must function, not as the general requirement of the Establishment Clause, but only as a rule for the particular class of establishment cases involving government-sponsored religious symbols and expression. The no-endorsement test is legitimate for that category of cases, I argue, but only because in those cases it serves the more fundamental goal of protecting a voluntary religious sector independent of government.
Keywords: Religious symbols; Establishment clause (Constitutional law); Free exercise clause (Constitutional law); Standard of review (Law); Sandra Day O& #x27; Connor; 1930-; William H. Rehnquist; 1924-2005; United States. Supreme Court; Church and state; Endorsements (Law); Freedom of religion; United States Constitution; United States